The Factors Constituting Mu’tazile’s Perception Related to Musebbihe -A Analysis in Context of the Âyats of the Divine Attributes- - Öğmüş, Harun (Yediveren Kitap, 2009)
Mu’tazile is the most reactive group to anthropomorphism in the theological madhabs. Their reaction contains the following groups: a. The sects named "Gulât" in the extreme anthropomorphism. b. The Salefiyye who believe the attributes of Allah including yed (hand), vech (face), ayn (eye), istivâ (sitting) etc. are used in Koran related to Him, but they tell that expressions do not point to the organs of the people, they say: they believe in these and do not know how they are. c. The other Sunnî groups who separate yed, istivâ etc. from the other attributes and they say the first sort of them are metaphor. In this article, it is searched the factors of Mu’tazile’s attitude in this topic and is fixed that the biggest factor in it is their polemics with non-Muslim groups, especially the Christians madhabs in the early times of their coming on the scene.

Kelâmî mezhepler içerisinde antropomorfizme karşı en şiddetli tepkiyi gösteren Mu’tezile’dir. Onların tepkisi aşağıdaki grupları kapsar: a. Antropomorfizme düşmüş olan Gulât adındaki marjinal kesimler; b. Kur’an’da Allah hakkında kullanılan yed, vech, ayn, istivâ vb de dahil olmak üzere Allah’ın bütün sıfatlarına inanan, fakat bu ifadelerin insanların organlarını göstermediğini belirten Selefiyye. Onlar bu nitelemelere inandıklarını fakat nasıl olduğunu bilmediklerini söylerler. c. Yed ve istivâ gibi sıfatları diğerlerinden ayıran birinci tür sıfatların mecaz olduğunu belirten Sünnî gruplar. Bu makalede, Mu’tezile’nin bu konudaki tutumunun sebepleri araştırılıyor ve bu sebeplerin en önemlisinin, ortaya çıktıkları ilk zamanlarda gayr-ı Müslimlerle, özellikle de Hıristiyan mezheplerle girdikleri polemikler olduğu tespit ediliyor.
Mu’tezile’nin Müşebbihe Algısını Oluşturan Amiller: Sıfat Ayetleri Bağlamında Bir Tahlil
Keywords: Religion, Society and Culture Studies; Din, Toplum ve Kültür Araştırmaları